PENGARUH PERSEPSI KEBERMANFAATAN, KEMUDAHAN, DAN RISIKO TERHADAP MINAT PENGGUNAAN LAYANAN PEMBAYARAN DIGITRAL PADA MAHASISWA AKUNTANSI - Nesha Nenandha (Jurnal Ekonomi Trisakti, 2022)
People in Indonesia are starting to get used to using a digital payment system that can be done anywhere and anytime during transaction activities. Therefore, the researcher conducted a study entitled: "The Influence of Perceived Usefulness, Perceived ease of use, and Perceived Risk in Using Digital Payment Services in Accounting Students." The purpose of this study is to examine the factors that influence the interest in using digital payment services. The method used is a quantitative approach with a sample of 95 accounting students at Trisakti University as users of digital payments. The data analysis method used in this study used descriptive analysis, validity, reliability, normality, multicollinearity, autocorrelation, multiple linear, f-test, and coefficient determination tests. The result of the research is that the perception of usefulness and the perception of convenience have a positive and significant effect on interest in use, while the perception of risk has a negative effect on interest in use.